α-Synuclein Regulates Peripheral Insulin Secretion and Glucose Transport - Wijesekara, Nadeeja; Ahrens, Rosemary; Wu, Ling; Langman, Tammy; Tandon, Anurag; Fraser, Paul E. (Frontiers in Aging Neuroscience, 2021)
Aim Population based studies indicate a positive association between type 2 diabetes (T2D) and Parkinson’s disease (PD) where there is an increased risk of developing PD in patients with T2D. PD is characterized by the abnormal accumulation of intraneuronal aggregated α-synuclein (α-syn) in Lewy bodies, which negatively impact neuronal viability. α-syn is also expressed in both pancreatic islets and skeletal muscle, key players in glucose regulation. Therefore, we examined the functional role of α-syn in these tissues. Methods Using mice lacking, overexpressing or transiently injected with α-syn, effects on glucose and insulin tolerance and insulin secretion were determined, with further characterization of the effects on GLUT4 translocation using GLUT4myc myotubes. Results Mice genetically ablated for α-syn became glucose intolerant and insulin resistant with hyperinsulinemia and reduced glucose-stimulated insulin secretion (GSIS). Mice overexpressing human α-syn are more insulin senstive and glucose tolerant compared to controls with increased GSIS. Injection of purified α-syn monomers also led to improved glucose tolerance and insulin sensitivity with hightened GSIS. α-syn monomer treatments increased surface GLUT4 levels in myotubes but without any significant change in Akt phosphorylation. The increase in cell surface GLUT4 was largely due to a large reduction in GLUT4 endocytosis, however, with a compensatory reduction in GLUT4 exocytosis. Conclusion Cumulatively, this data suggests that α-syn modulates both pancreatic beta cell function and glucose transport in peripheral tissues, thereby playing a pivitol role in the maintenance of normal glucose homeostasis.